Lessons for change: getting more from international forestry assistance - Fruhling, P.; Persson, R. (SIDA and CIFOR, 2001)
During the last few decades, forestry assistance has benefited from the positive interest in environmental issues and has generally been less questioned than many other sectors of fields within international development assistance. If compared with its own goals and the resources invested, it have achieved rather modest results. The privileged position of forestry assistance may thus soon be challenged, by legitimate demands for increases efficiency in times of decreasing overall volumes of international development aid. Now it is time to embark upon the discussion on how to improve quality and effectiveness, how to spend smarter or even how to do more with less. The purpose of this booklet is to contribute to this much-needed discussion, drawing upon relevant lessons learnt within other fields of international development assistance, analyzing the current situation concerning forestry assistance and finally outlining some suggestions on new paths for the future.